Covalent Organic Frameworks as a Decorating Platform for Utilization and Affinity Enhancement of Chelating Sites for Radionuclide Sequestration. Issue 20 (27th March 2018) - Sun, Qi; Aguila, Briana; Earl, Lyndsey D.; Abney, Carter W.; Wojtas, Lukasz; Thallapally, Praveen K.; Ma, Shengqian
Abstract: The potential consequences of nuclear events and the complexity of nuclear waste management motivate the development of selective solid‐phase sorbents to provide enhanced protection. Herein, it is shown that 2D covalent organic frameworks (COFs) with unique structures possess all the traits to be well suited as a platform for the deployment of highly efficient sorbents such that they exhibit remarkable performance, as demonstrated by uranium capture. The chelating groups laced on the open 1D channels exhibit exceptional accessibility, allowing significantly higher utilization efficiency. In addition, the 2D extended polygons packed closely in an eclipsed fashion bring chelating groups in adjacent layers parallel to each other, which may facilitate their cooperation, thereby leading to high affinity toward specific ions. As a result, the amidoxime‐functionalized COFs far outperform their corresponding amorphous analogs in terms of adsorption capacities, kinetics, and affinities. Specifically, COF‐TpAb‐AO is able to reduce various uranium contaminated water samples from 1 ppm to less than 0.1 ppb within several minutes, well below the drinking water limit (30 ppb), as well as mine uranium from spiked seawater with an exceptionally high uptake capacity of 127 mg g −1 . These results delineate important synthetic advances toward the implementation of COFs in environmental remediation. Abstract : Ordered pore structure matters : greatly improved accessibility and affinity of binding sites in adsorbents designed from well‐defined channels, relative to those prepared from materials with disordered pore networks, are delineated. Specifically, covalent‐organic‐framework‐based sorbents far outperform their amorphous analogs in the mitigation of uranium from various water samples, able to drop below the drinking water limit and mine uranium from seawater.